A model for the differentiation between grid and conjunctive units in medial entorhinal cortex. Issue 12 (22nd September 2013) - Si, Bailu; Treves, Alessandro
ABSTRACT The multiple layers of medial entorhinal cortex (mEC) contain cells that differ in selectivity, connectivity, and cellular properties. Grid cells in layer II and in the deeper layers express triangular grid patterns in the environment. The firing rate of the conjunctive cells found in layer III and below, on the other hand, show grid‐by‐head direction tuning. In this study, we model the differentiation between grid and conjunctive cells in a network with self‐organized connections. Arranged into distinct "layers", the model grid units and conjunctive units develop, with a similar time course, grid fields resulting from firing rate adaptation and competitive learning. Grid alignment in both layers is delayed with respect to the formation of triangular grids. A common grid orientation among conjunctive units is produced, in the model, by head‐direction modulated collateral interactions, while the grids of grid units inherit the same orientation through connections from conjunctive units. Grid units as well as conjunctive units share a similar spacing but show a random distribution of spatial phases. Grid units however carry more spatial information than conjunctive units, thus providing better inputs for the hippocampus to form spatial memories. © 2013 Wiley Periodicals, Inc.